Güncel Üroloji Çalışmaları V (Bahar) - Altun, Ertürk; Tok, Doğan Sabri; Loglı, Ridell; Hasırcı, Eray; Ceylan, Şule; Çolak, Fatih; Cincorop, Serdar; Atkın, Mehmet Sinan; Aksoy, Hamit Zafer; Akça, Görkem; Kazaz, İlke Onur; Atnallar, Göktuğ; et al. (2024)
-